PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP MOTIVASI DAN AKTIVITAS BELAJAR MATEMATIKA SISWA - Tengku Tiara Insan Ramadhani; Tasnim Rahmat (STKIP Subang, 2026)
The low levels of students' motivation and learning activities in mathematics have contributed to suboptimal learning outcomes. One effort to address this problem is the implementation of the Think Pair Share (TPS) cooperative learning model, which encourages students to think independently, discuss with a partner, and share the results of their discussion, thereby increasing student engagement in the learning process. This study aimed to determine the effect of the Think Pair Share (TPS)cooperative learning model on students' mathematics learning motivation and learning activities. This study employed a pre-experimental method using a One Group Pretest–Posttest Design. The sample consisted of 29 students from class XI TPM 1, selected using the simple random sampling technique. Data were collected through mathematics learning motivation and learning activity questionnaires based on a Likert scale that had met the validity and reliability requirements. The data were analyzed using normality, homogeneity, and paired sample t-test analyses. The results showed that the mean score of learning motivation increased from 124.45 on the pretest to 150.07 on the posttest, while the mean score of learning activities increased from 136.97 to 152.48. The hypothesis testing indicated that learning motivation obtained a t-value of 12.4045 with a significance value of 0.000 (< 0.05), while learning activities obtained a t-value of 11.8632 with a significance value of 0.000 (< 0.05), indicating a statistically significant effect. Therefore, it can be concluded that the implementation of the Think Pair Share (TPS) cooperative learning model has a significant effect on improving students' mathematics learning motivation and learning activities